Mega Clonality in an Aquatic Plant—A Potential Survival Strategy in a Changing Environment - Bricker, Eric; Calladine, Ainsley; Virnstein, Robert; Waycott, Michelle (Frontiers in Plant Science, 2018)
Many ecosystems are experiencing rapid transformations due to global environmental change. Understanding how ecological shifts affect species persistence is critical to modern management strategies. The edge of a species range is often where physiological tolerances are in conflict with ability to persist. Extreme examples of clonality over large spatial and temporal scales can occur where the life history of a species allows for it. We examine extreme clonality in an aquatic plant species at the edge if its range. Here we describe an ancient seagrass clone of unprecedented size inhabiting a 47 km stretch of a central Florida estuary, the Indian River Lagoon (IRL). Amongst the largest clones on earth detected, this Thalassia testudinum (turtlegrass) genet had ramets dispersed across 47 km of this water body. Indeed among 382 samples collections along the length of the IRL, 89% were a single shared multilocus genotype. Furthermore, this clone was the only genet detected at 63% of sample sites. The presence of such a large clone demonstrates they can form and persist over long periods. In addition, we must challenge the paradigm that fragmentation is not possible in this species. Reliance on clonality is an expected component of a classic 'bet-hedging' strategy enabling persistence on timescales typically not considered, including millennia. At locations near ocean inlets we did find a few other individuals of T. testudinum supporting the concept that recruitment is dispersal limited. These additional clones indicate there is the potential, albeit limited, for seeds based recruitment to occur when environmental conditions are favorable during a "window of opportunity" . Extreme clonality represents a potential strategy for survival such that in the extreme, clonal populations of a species would be the first to decline or disappear if conditions extend beyond the adaptability of the local genotype. This disappearance possibility makes the species a potential sentinel of system decline.